Social media usage for language literacy development in Indonesia - Hadiapurwa, Angga; Joelene, Eileen Nicole; Nugraha, Hafsah; Komara, Diemas Arya (Universitas Padjadjaran, 2023)
The development and emergence of social media have pushed literacy and language activities in new directions. The increasing social media usage affects various language literacy activities by optimizing the existence of social media. This study aimed to determine the relationship between social media usage and the improvement of language literacy, especially in language learning, so there would be recommendations in the form of efforts to improve language literacy skills. This research would fill gaps in understanding how social media features and activities could effectively develop language literacy. Data collection used the literature study method from primary and secondary sources discussing literacy, language learning, and social media. The literature found was checked first, organized, and matched with the thematic framework to continue content analysis and description. Social media had many opportunities as a facilitator of language literacy development, and its presence would push other activities to perform better. It needed a proper method to make the result significant, notably for the incredible impact on language learning. So, apart from being a means of developing language learning, social media can also have the negative side of damaging the user's first language because other languages and cultures absorb it. Other factors such as family contribution, educational background and its influence on first and second language learning, sociological side, and all learning obstructions should be addressed when developing language skills. The study’s findings will provide recommendations for utilizing social media platforms to enhance reading, writing, and critical thinking skills.